STRENGTHENING 21ST CENTURY SKILLS THROUGH AN INDEPENDENT CURRICULUM IN MATHEMATICS EDUCATION IN INDONESIA: CHALLENGES, POTENTIAL, AND STRATEGIES - Masjudin MASJUDIN (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2024)
Several research results show that 21st century skills such as critical, creative, collaborative and communicative thinking in Indonesian students are not as expected. Then the Ministry of Education and Culture launched the Independent Curriculum as an effort to improve the quality of education and adapt it to the needs of the times. The aim of this research is to identify the challenges, potential and strategies for implementing the Independent Curriculum in strengthening 21st century skills in mathematics education in Indonesia. This research is a Systematic Literature Review (SLR) which examines various literature sources. The research results show that the Merdeka Curriculum has great potential in supporting the development of 21st century skills. The Merdeka Curriculum provides flexibility in learning, encourages creativity and critical thinking through a student-centred approach, and strengthens collaboration and communication skills. However, implementation faces challenges such as lack of resources, teacher preparedness, resistance to change, and the need for more flexible evaluation. The Merdeka Curriculum requires an implementation strategy that includes teacher training, development of innovative materials, technology integration, and ongoing evaluation